Learning & Development in Times of Digital Transformation: Facilitating a Culture of Change and Innovation - Vey, Karin; Fandel-Meyer, Tanja; Zipp, Jan S.; Schneider, Christian (International Journal of Advanced Corporate Learning (iJAC), 2017)
The digital transformation is the very heart of the Fourth Industrial Revolution, which is about to change our understanding of doing business, of learning & development in a fundamental way – and with unrivaled speed. However, many companies and individuals hesitate to acknowledge the depth and impact of current developments. We suggest to distinguish four reasons: the striking impact of advanced digitization is not yet fully recognized (1); there is a lack of imagination and strategy, coupled with increasing unpredictability (2); a lack of agility and insufficient encouragement towards innovation (3); and a lack of pertinent competencies and insufficient innovation culture (4). New roles and action areas for Learning & Development (L&D) professionals enable possibilities to overcome these innovation barriers: change agent & consultant; designer of an enriched learning portfolio of products and services; shaper of innovation culture. Also facilitating a learning friendly culture by using different pillars is a way to generate innovation and to secure the existence of organizations in times of digital transformation.